2011
DOI: 10.3109/03009742.2011.608376
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome in patients with juvenile dermatomyositis: a cross-sectional follow-up study

Abstract: In a long-term follow-up study, 60% of JDM patients had disease damage at a mean of 14 years after disease onset. Longer disease duration was the most important predictor of damage, calcinosis, and impaired muscle function, and higher age at disease onset predicted more organs involved at follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 25 publications
4
64
4
1
Order By: Relevance
“…Higher initial levels of serum creatine kinase and prolonged elevation of muscle enzymes have been associated with calcinosis as well [5,35]. An association with lipodystrophy and panniculitis may be seen due to the fact these complications are also associated with severe and prolonged disease [8,9,36]. A large international multicenter study found that calcinosis in JDM is associated with earlier year of onset, older age at onset, chronic polycyclic or chronic continuous illness course, and increased disease duration [8].…”
Section: Risk Factors For Calcinosismentioning
confidence: 99%
See 1 more Smart Citation
“…Higher initial levels of serum creatine kinase and prolonged elevation of muscle enzymes have been associated with calcinosis as well [5,35]. An association with lipodystrophy and panniculitis may be seen due to the fact these complications are also associated with severe and prolonged disease [8,9,36]. A large international multicenter study found that calcinosis in JDM is associated with earlier year of onset, older age at onset, chronic polycyclic or chronic continuous illness course, and increased disease duration [8].…”
Section: Risk Factors For Calcinosismentioning
confidence: 99%
“…A large international multicenter study found that calcinosis in JDM is associated with earlier year of onset, older age at onset, chronic polycyclic or chronic continuous illness course, and increased disease duration [8]. Analysis of a Danish cohort, including long-term follow-up, confirmed disease duration greater than 4 years to be a risk factor for calcinosis [9]. Another multicenter registry has described an association of calcinosis with African American race, even after adjustment for duration of disease and time to rheumatologic care [37].…”
Section: Risk Factors For Calcinosismentioning
confidence: 99%
“…Registries of larger size are required to determine the relevance of these factors in predicting disease course. Furthermore, calcinosis, lipodystrophy and cutaneous ulcerations are not typically present at onset or diagnosis, as analysed in this study, but have been found in some cohorts to be associated with a chronic illness course or longstanding active disease in patients with JIIM (5,25). …”
Section: Discussionmentioning
confidence: 64%
“…We have categorized this listing of myositis research registries into different groups (see Tables 1, 2, and 3) [13**,14,15*,1628,29*,30*,3137,38*,3942,43* 44,45,46*,4760,61**,62,63*,64*,65, 66*,67,68**,69*,70*,71,72*,7382,83*,8490,91*,92107,108*,109,110**,111** 112115,116*,117, 118*,119121, 122**,123129, 130*,131133,134*,135,136*, 137–149,150*,151,152,153*,154*] based on the types of myositis included, as well as whether the registries are regional, national, or international in scope. Thirteen registries are international and 33 are national or regional registries.…”
Section: Myositis Registries and Biorepositoriesmentioning
confidence: 99%
“…Tools such as the Myositis Damage Index have enabled further understanding of long-term outcomes and the appreciation that most adult and juvenile myositis patients have moderate to severe damage on long-term follow-up as well as ongoing active disease [81,148;,149,151, 152,159,160]. Interest in long-term outcomes and prognosis has also received attention more generally, including the recognition of risk factors for chronic illness course in JDM [35,104], associated malignancies or autoimmune overlap syndromes [36,37,66*], or certain sequelae of disease, such as calcinosis, lipodystrophy [100,104,113], premature cardiovascular disease, and metabolic syndrome [38*,69*,147].…”
Section: Research Advances Through Myositis Registries and Biorepositmentioning
confidence: 99%